Implementation Of Reading Corner In Developing Reading Interest Of Grade 2 Students Of SDN 5 Sigar Penjalin In The 2023/2024 Academic Year - Rusmiati, Rusmiati; Hadi, Rusman; Mulyono, Ana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this research is to determine how the reading corner is implemented to foster reading interest among second-grade students of SDN 5 Sigar Penjalin in the 2023-2024 academic year. Understanding and utilizing reading and writing is the primary goal of the reading corner as a teaching strategy. Second-grade students serve as research subjects for this study. This research is of a qualitative type. The results of the study show that the reading corner at SDN 5 Sigar Penjalin can enhance students' reading interest. The implementation of the reading corner at SDN 5 Sigar Penjalin involves several methods to help students develop their reading interest, including encouraging students to read before starting lessons, listening to stories, and reading to boost their interest in reading..